16th IHIW: Population Global Distribution of Killer Immunoglobulin‐like Receptor (KIR) and Ligands. (26th December 2012) - Hollenbach, J. A.; Augusto, D. G.; Alaez, C.; Bubnova, L.; Fae, I.; Fischer, G.; Gonzalez‐Galarza, F. F.; Gorodezky, C.; Karabon, L.; Kusnierczyk, P.; Noble, J.; Rickards, O.; et al.
Summary In the last fifteen years, published reports have described KIR gene‐content frequency distributions in more than 120 populations worldwide. However, there have been limited studies examining these data in aggregate to detect overall patterns of variation at regional and global levels. Here, we present a summary of the collection of KIR gene‐content data for 105 worldwide populations collected as part of the 15th and 16th International Histocompatibility and Immunogenetics Workshops, and preliminary results for data analysis.